Variables associated with the fluctuation of Rhynchophorus palmarum (COLEOPTERA: CURCULIONIDAE) in influence area of oil palm and american oil palm in the Central Amazônia - Cysne, Alex Queiroz; Rios, Sara de Almeida (Scientia Agraria Paranaensis, 2017)
Rhynchophorus palmarum (L.) is one of the main pests of economic importance in the cultivation of American oil palms. This work aimed to evaluate the influence of the management practices and environmental variables in the population of R. palmarum in area of seed production of Elaeis spp. in the Amazonas State, Brazil. The climate data (temperature, relative humidity, and rainfall), seed production (number of harvested bunches, number of female inflorescences) and capture of insects (traps baited with pheromone of aggregation and sugar cane (Saccharum officinarum L.)) were collected, and subjected to statistical analysis, multiple linear regression, and Pearson’s correlation. It was observed that rainfall, minimal relative humidity and harvest of bunches in American oil palm influenced the population of R. palmarum. These variables should be considered in the implementation of management activities for this pest.